Fine‐scale changes in connectivity affect the metapopulation dynamics of a bryophyte confined to ephemeral patches - Zartman, Charles E.; Nascimento, Henrique E. M.; Cangani, Katia G.; Alvarenga, Lisi D. P.; Snäll, Tord (The Journal of ecology, 2012)
1. We test how fine‐scale (≤ 400 m2) connectivity to conspecifics influences metapopulation dynamics using a field experiment in central Amazonia with the epiphyllous (i.e. leaf‐inhabiting) bryophyte Radula flaccida Gott. (Radulaceae). This is a natural model system with spatially structured ephemeral patches at the leaf and phorophyte scale. 2. The aim was to test how the rates of leaf colonization, local abundance, growth and extinction of bryophytes from both leaves and host phorophytes were affected by experimentally manipulated variation in connectivity to conspecifics. We also investigated the relative importance of local stochastic extinctions and deterministic extinctions at both spatial scales. 3. Approximately 3500 leaves on 70 phorophytes were censused six times over a 15‐month period by utilizing a repeated block design with control, positive control and three pulse‐style reduction treatments, which varied in connectivity to surrounding conspecifics. 4. An increase in stochastic extinction events was only accompanied by a reduction in colonization in the treatment in which focal and neighbouring phorophytes within the 400 m2 plots were experimentally denuded of their natural populations, suggesting that epiphyllous cryptogams are subject to fine‐scale (within phorophyte) rescue effects. Negative density‐dependent growth was also detected in within‐leaf population dynamics, suggesting that resource limitation or intraspecific competition influences local population growth. Finally, stochastic extinctions from viable leaves occurred with nearly the same frequency as deterministic events (e.g. leaf fall), whereas at the phorophyte scale only stochastic extinctions were observed. 5. Synthesis. The experiment demonstrates that rescue effects occur at fine scales even for vagile plant taxa, such as cryptogams, which may inhabit spatially isolated substrates characterized by turnover rates as fast as their own population dynamics. Furthermore, the results highlight the importance of quantifying both stochastic and deterministic extinction modes, as underestimating either of these parameters leads to over optimistic projections of future metapopulation size.